2012
DOI: 10.1002/pits.21663
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peer Attachment and Normative Beliefs About Aggression on Traditional Bullying and Cyberbullying

Abstract: This study examined the effects of normative beliefs about aggression and peer attachment on traditional bullying, cyberbullying, and both types of victimization. Cyberbullying departs from traditional forms of bullying in that it is through forms of technology, such as the Internet, which increases situational anonymity. Eight hundred fifty students in Grades 6 through 8 completed a survey that assessed normative beliefs about aggression, peer attachment, and traditional bullying and cyberbullying behaviors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(118 citation statements)
references
References 52 publications
8
98
0
12
Order By: Relevance
“…Peer attachment is one variable that has been examined in association with cyberbullying involvement, and it has been identified as serving either as a risk or mitigating factor, depending on adolescents' endorsement of low or high levels of peer attachment (Burton, Florell, & Wygant, 2013). Some research on cyberbullying and cyber aggression involvement has been conducted in countries other than the United States and Europe, revealing these behaviors as a global concern.…”
mentioning
confidence: 98%
“…Peer attachment is one variable that has been examined in association with cyberbullying involvement, and it has been identified as serving either as a risk or mitigating factor, depending on adolescents' endorsement of low or high levels of peer attachment (Burton, Florell, & Wygant, 2013). Some research on cyberbullying and cyber aggression involvement has been conducted in countries other than the United States and Europe, revealing these behaviors as a global concern.…”
mentioning
confidence: 98%
“…Studies have also shown a relationship between greater perceived acceptability of aggressive behaviors and greater intention to act aggressively (Ang, Tan, & Mansor, 2010;Burton, Florell, & Wygant, 2013;Gracia & Herrero, 2006;Huesmann & Guerra, 1997;Huesmann et al, 1992;Krahé & Möller, 2004;Möller & Krahé, 2008;Zhen et al, 2011). Ang et al (2010) and Burton et al (2013) found that those who believed aggression is acceptable behavior were more likely to engage in cyberbullying.…”
Section: Flaming Acceptability and Flaming Intentionmentioning
confidence: 93%
“…Ang et al (2010) and Burton et al (2013) found that those who believed aggression is acceptable behavior were more likely to engage in cyberbullying. Similarly, Krahé and Möller (2004) and Zhen et al (2011) both found that perceived acceptability of aggression tactics was related to intention to engage in aggressive behaviors.…”
Section: Flaming Acceptability and Flaming Intentionmentioning
confidence: 96%
“…However, peer influence might not be exclusively related to behavioral patterns, but also to beliefs about aggression and bullying (Burton et al 2013;Huesmann & Guerra 1997;Salmivalli & Voeten, 2004;Van Goethem et al 2010). Huesmann and Guerra (1997) defined normative beliefs as the cognitions regarding the acceptability or unacceptability of certain behaviors, considering also emotional reactions.…”
Section: Adolescent Social Norms and Beliefs: Setting The Stage Of Whmentioning
confidence: 99%